Efficacy of Probiotic Strains Lactobacillus sakei Probio65 and Lactobacillus plantarum Probio-093 in Management of Obesity: An In Vitro and In Vivo Analysis - Aneela Gulnaz; Lee-Ching Lew; Yong-Ha Park; Jamal S. M. Sabir; Raed Albiheyri; Irfan A. Rather; Yan-Yan Hor (MDPI AG, 2024)
The prevalence of obesity, characterized by an excessive accumulation of adipose tissue and adipocyte hypertrophy, presents a major public health challenge. This study investigates the therapeutic potential of two probiotic strains, Lactobacillus sakei Probio65 and Lactobacillus plantarum Probio-093, in the context of obesity. Utilizing 3T3-L1 cell-derived human adipocytes, we assessed Probio65's and Probio-093's capacity to mitigate triglyceride accumulation and influence adipocytokine production in vitro. Subsequently, an in vivo trial with male C57BL/6J mice examined the effects of both probiotic strains on adipose tissue characteristics, body weight, fat mass, and obesity-related gene expression. This study employed both live and ethanol-extracted bacterial cells. The results demonstrated significant reductions in the triglyceride deposition, body weight, and adipose tissue mass in the treated groups (p < 0.05). Furthermore, both strains modulated adipokine profiles by downregulating proinflammatory markers such as PAI-1, leptin, TNF-α, STAMP2, F4/80, resistin, and MCP-1, and upregulating the insulin-sensitive transporter GLUT4 and the anti-inflammatory adiponectin (p < 0.05). Our findings suggest that Lactobacillus sakei Probio65 and Lactobacillus plantarum Probio-093 are promising agents for microbiome-targeted anti-obesity therapies, offering the effective mitigation of obesity and improvement in adipocyte function in a murine model.